B2.4 Rapid paediatric sequencing (raps) in critically ill children at great ormond street hospital. (4th October 2017) - Clement, E; Boukhibar, L; Jones, W; Hurst, J; Scott, R; Chitty, L; Bitner-Glindzicz, M; Peters, M; Williams, H; Beales, P
Abstract : Background: Great Ormond Street Hospital cares for many children with rare and complex disease. A substantial proportion of these children will have an underlying genetic cause for their condition. Making a diagnosis in such cases is increasingly achievable due to advances in genomic testing. However, such testing may not be available on the NHS and results, when accessed in the research setting, typically take many months to report. In critically ill children, cared for on the intensive care units, a timely genetic diagnosis may be beneficial on a number of levels. It may inform treatment options and prognosis. It may also reduce the need for further investigations, improving the diagnostic odyssey and potentially reducing costs. In addition, it may help the family understand recurrence risks. Methods: To address this unmet need we developed a work flow to enable Rapid Paediatric Sequencing (RaPS) in critically ill children. Eligible patient-parent trios were recruited and underwent whole genome sequencing. A framework was developed to allow capture of clinical information and robust analysis of genomic data initially by investigating candidate gene lists and HPO-derived panels. If no genetic diagnosis was forthcoming, genomic analysis was broadened and more disease-causing genes were investigated. Results: Twenty two patient-parent trios were recruited to the RaPS pilot project. A diagnosis was reached in 8 cases (36%). The shortest turnaround time from sample collection to return of provisional results was 5 days. A genetic diagnosis informed point of care decisions in at least 3 cases. Conclusion: We report on the process and framework necessary to deliver rapid whole genome sequencing to critically ill paediatric patients and reflect on the outcomes, clinical utility and challenges of implementing such a service at GOSH.